Factors Affecting Purchasing Decisions for Leather Craft: Price, Quality, and Service: Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Produk Kerajinan Kulit: Harga, Kualitas, dan Layanan. - Muchammad Rifta Indra Yulian; Detak Prapanca (Universitas Muhammadiyah Sidoarjo, 2023)
This causal quantitative research examines the impact of price, product quality, and service quality on purchasing decisions for leather craft products. The study utilizes accidental sampling with 98 respondents, and data collection is done through a questionnaire measured using a Likert scale. Multiple linear regression analysis is employed for data analysis. The findings demonstrate that there is a significant simultaneous and partial effect of price, product quality, and service quality on purchasing decisions. Service quality emerges as the most dominant factor influencing purchasing decisions, as evidenced by the beta coefficient. Moreover, the strong relationship between price, product quality, service quality, and purchasing decisions is substantiated by a high R value. These findings have implications for businesses in the leather craft industry, highlighting the importance of pricing strategies, product quality, and exceptional service to drive customer purchasing decisions. Highlights: This quantitative causal study explores the impact of price, product quality, and service quality on purchasing decisions for leather craft products. Accidental sampling was used to select 98 respondents, and data were collected through a Likert scale questionnaire. The findings indicate a significant influence, both individually and collectively, of price, product quality, and service quality on purchasing decisions. Service quality emerges as the most influential factor, emphasizing the importance of exceptional customer service in driving purchasing decisions for leather craft products. Keywords: Price, Product quality, Service quality, Purchasing decisions, Leather craft products.